The rough guide to Europe on a budget 2025 - Beattie, Andrew; Stables, Daniel; Williams, Beth (Travel editor); Reeves, Joanna (Travel writer) (Rough Guides, 2025)
Blends must-see sights with hidden gems and offers unmatched practical guidance for seamless planning and on-the-go exploration. Packed with in-depth advice often missing from other guides, it helps you navigate with ease. From using public transport to discovering the best dining, accommodations, and local experiences, this guide covers it all. Every detail you need for a smooth and enriching journey.